OPTIMALISASI PROSES PRODUKSI DENGAN PENDEKATAN METODE SIMPLEKS STUDI KASUS PADA PIZZA HUT - mafin, mafin dwi handoko (PT. ANAN PUBLISHER CENDEKIA, 2025)
The fast food industry encounters significant challenges in optimizing its production processes to remain competitive. This research employs the simplex method to optimize the production process at Pizza Hut, with the aim of reducing operational costs while maintaining product quality. Data collected from Pizza Hut's operational records for one month, including order volume, production time, and raw material costs, were analyzed. The results demonstrate that the simplex method improve the efficiency of using raw materials by up to 12% and significantly reduce waste. Validation of the model with actual data shows a margin of error of 3%, affirming the relevance of this approach in the management of fast food production.